Construction, PPy loading and photocatalytic performance of a polyoxometalate-templated metallacycle compound. Issue 19 (2nd October 2017) - Wang, Yu-Guang; Zhu, Pei-Pei; Li, Xiao; Zhou, Kun-Feng; Yang, Jian-Bo; Ma, Xiao-Liang; Sha, Jing-Quan
Abstract: A polyoxometalate-templated metallacycle compound, [Ag6 trz6 ][H3 PMo12 O40 ]2 ·6H2 O (trz = 1, 2, 3-triazole), has been isolated and structurally characterized. The compound represents the first example of a trigonal antiprism based metal-organic framework (MOFs) with complicated Zr6 Br12 type topology, in which the trigonal antiprisms as building blocks are constructed by the Ag6 trz6 space polygons and the bifunctional POMs (both as template and building block). In addition, to improve the photocatalytic activity of polyoxometalate-templated metallacycle compound, polypyrrole was loaded on its surface through a chemical oxidation polymerization process in situ . Finally, the photocatalytic activity of [Ag6 trz6 ][H3 PMo12 O40 ]2 and PPy@[Ag6 trz6 ][H3 PMo12 O40 ]2 under visible light was explored, and the results demonstrate that the PPy loading on the surface of POMs-based hybrid compound is feasible to improve their photocatalytic performance. Abstract :